Prognostic values of long noncoding RNA in bone metastasis of prostate cancer: A systematic review and meta-analysis - Song, Silu; Zhu, Yanli; Zhang, Xue; Chen, Siyu; Liu, Shuang (Frontiers in Oncology, 2023)
Background: Recent studies have shown that long non-coding RNAs are closely related to the occurrence and development of prostate cancer bone metastasis, and can be used as biomarkers to predict the prognosis of patients. Therefore, this study aimed to systematically evaluate the relationship between the expression levels of long non-coding RNAs and the prognosis of patients. Methods: The studies of lncRNA in prostate cancer bone metastasis from Pubmed, Cochrane library, Embase, Ebsco, Web of science, Scopus, Ovid databases were analyzed, and Stata 15 was used for meta-analysis. Associations between lncRNA expression and patients' overall survival (OS) and bone metastasis-free survival (BMFS) were assessed by correlation analysis with pooled hazard ratios (HR) and 95% confidence intervals (CI). Furthermore, the results were validated using GEPIA2 and UALCAN, online database based on TCGA. Subsequently, the molecular mechanisms of the included lncRNAs were predicted based on the LncACTdb 3.0 database and the lnCAR database. Finally, we used clinical samples to validate lncRNAs that were significantly different in both databases. Results: A total of 5 published studies involving 474 patients were included in this meta-analysis. The results showed that lncRNA overexpression was significantly associated with lower OS (HR = 2.55, 95% CI: 1.69 - 3.99, p < 0.05) and lower BMFS (OR = 3.16, 95% CI: 1.90 - 5.27, p < 0.05) in patients with prostate cancer bone metastasis. Based on validation from the GEPIA2 and UALCAN online databases, SNHG3 and NEAT1 were significantly up-regulated in prostate cancer. Further functional prediction showed that the lncRNAs included in the study were involved in regulating the occurrence and development of prostate cancer through the ceRNA axis. The result of clinical samples showed that SNHG3 and NEAT1 were expressed in prostate cancer bone metastasis at higher levels than in primary tumors. Conclusions: LncRNA can be used as a novel predictive biomarker for predicting poor prognosis in patients with prostate cancer bone metastasis, which is worthy of clinical validation.